Virtual mentalizing imagery therapy for Spanish language Latino family dementia caregivers: A feasibility and acceptability study - Ramirez-Gomez, Liliana; Johnson, Julene K.; Ritchie, Christine; Meyer, Ashley K.; Tan, Emily; Madarasmi, Saira; Gutierrez-Ramirez, Paulina; Aldarondo-Hernández, Cecilianna; Mischoulon, David; Banerjee, Sreya; Jain, Felipe A. (Frontiers in Psychology, 2023)
Spanish speaking family caregivers of people living with dementia have limited supportive resources in Spanish. There are few validated, culturally acceptable virtual interventions for reducing these caregivers’ psychological distress. We investigated the feasibility of a Spanish language adaptation of a virtual Mentalizing Imagery Therapy (MIT), which provides guided imagery and mindfulness training to reduce depression, increase mentalizing, and promote well-being. 12 Spanish-speaking family dementia caregivers received a 4-week virtual MIT program. Follow-up was obtained post group and at 4 months post baseline assessment. Feasibility, acceptability, and satisfaction with MIT were assessed. The primary psychological outcome was depressive symptoms; secondary outcomes included caregiver burden and dispositional mindfulness. Statistical analysis was performed with mixed linear models. Caregivers were 52±8 (mean±SD) years of age; 60% had a high school education or less. Participation in weekly group meetings was 100%. Home practice was performed on average 4±1 times per week [range 2-5]. Satisfaction with MIT reached 19±2 of a possible 20 points. Reduction in depression from baseline was observed by week 3 (p=.01) and maintained at 4 month follow-up (p=.05). There were significant improvements in mindfulness post-group, and in caregiver burden and well-being at 4 months. Mentalizing Imagery Therapy (MIT) was successfully adapted for a sample of Latino Spanish language family dementia caregivers within a virtual group environment. MIT is feasible and acceptable and may help reduce depressive symptoms and improve subjective well-being. Larger, randomized controlled trials of MIT should determine durability of effects and validate efficacy in this population.